Sunscreen photoprotection and vitamin D status. (1st November 2019) - Passeron, T.; Bouillon, R.; Callender, V.; Cestari, T.; Diepgen, T.L.; Green, A.C.; van der Pols, J.C.; Bernard, B.A.; Ly, F.; Bernerd, F.; Marrot, L.; Nielsen, M.; et al.
Summary: Background: Global concern about vitamin D deficiency has fuelled debates on photoprotection and the importance of solar exposure to meet vitamin D requirements. Objectives: To review the published evidence to reach a consensus on the influence of photoprotection by sunscreens on vitamin D status, considering other relevant factors. Methods: An international panel of 13 experts in endocrinology, dermatology, photobiology, epidemiology and biological anthropology reviewed the literature prior to a 1‐day meeting in June 2017, during which the evidence was discussed. Methods of assessment and determining factors of vitamin D status, and public health perspectives were examined and consequences of sun exposure and the effects of photoprotection were assessed. Results: A serum level of ≥ 50 nmol L −1 25(OH)D is a target for all individuals. Broad‐spectrum sunscreens that prevent erythema are unlikely to compromise vitamin D status in healthy populations. Vitamin D screening should be restricted to those at risk of hypovitaminosis, such as patients with photosensitivity disorders, who require rigorous photoprotection. Screening and supplementation are advised for this group. Conclusions: Sunscreen use for daily and recreational photoprotection does not compromise vitamin D synthesis, even when applied under optimal conditions. What's already known about this topic? Knowledge of the relationship between solar exposure behaviour, sunscreen use and vitamin D is important for public health but there is confusion about optimal vitamin D status and the safest way to achieve this. Practical recommendations on the potential impact of daily and/or recreational sunscreens on vitamin D status are lacking for healthy people. What does this study add? Judicious use of daily broad‐spectrum sunscreens with high ultraviolet (UV) A protection will not compromise vitamin D status in healthy people. However, photoprotection strategies for patients with photosensitivity disorders that include high sun‐protection factor sunscreens with high UVA protection, along with protective clothing and shade‐seeking behaviour are likely to compromise vitamin D status. Screening for vitamin D status and supplementation are recommended in patients with photosensitivity disorders.